Quantum Entanglement and the Foundations of Modern Physics: A Conceptual Analysis of Non-Locality Theories - Wiwik Hidayati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Quantum entanglement and non-locality remain central to the foundations of modern physics, yet their conceptual status continues to generate theoretical and philosophical debate. This study presents a systematic conceptual analysis of non-locality theories by integrating geometric state-space formulations, ontological reconstructions, and Bell-type logical diagnostics. Geometric approaches demonstrate that entanglement arises from the complex projective structure of quantum state space and is formally equivalent to established separability and CHSH criteria in both multiparticle and continuous-variable systems. Ontological models reinterpret these results through diverse commitments, including holistic realism, global-state dependence, informational emergence of time, and conceptual relationalism, each proposing distinct mechanisms for non-local coordination. Logical and sheaf-theoretic frameworks recast Bell violations as structural obstructions to global value assignments rather than as superluminal influence. Experimental photonic systems, high-energy reconstructions, and quantum communication protocols confirm the operational robustness of Bell-type correlations under realistic noise conditions. The analysis demonstrates that non-locality functions simultaneously as geometric invariant, logical constraint, empirical signature, and technological resource. By comparatively reconstructing these dimensions, the study clarifies the conceptual architecture underlying quantum non-locality and refines its role within contemporary foundational physics.